2021
DOI: 10.1093/noajnl/vdab034
|View full text |Cite
|
Sign up to set email alerts
|

MR1 overexpression correlates with poor clinical prognosis in glioma patients

Abstract: Background Glioblastoma is the most common adult primary brain tumor with near universal fatality. Major histocompatibility complex (MHC) class-I molecules are important mediators of CD8 activation and can be downregulated by cancer cells to escape immune surveillance. MR1 is a non-classical MHC-I like molecule responsible for the activation of a subset of T cells. Although high levels of MR1 expression should enhance cancer cell recognition, various tumors demonstrate MR1 overexpression with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…The transcriptional data of TCGA-GBM revealed that high expression of MR1 was significantly correlated with GBM's poor survival. This observation was consistent with a previous report and was also confirmed by the CGGA database 4 . Comprehensive gene expression data analysis and the direct search of the raw sequence data of TCGA-GBM showed that 8.3% of the GBM samples had MAIT cell infiltration, and the intra-tumoral MR1 expression significantly correlated with the infiltration level of MAIT cells.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The transcriptional data of TCGA-GBM revealed that high expression of MR1 was significantly correlated with GBM's poor survival. This observation was consistent with a previous report and was also confirmed by the CGGA database 4 . Comprehensive gene expression data analysis and the direct search of the raw sequence data of TCGA-GBM showed that 8.3% of the GBM samples had MAIT cell infiltration, and the intra-tumoral MR1 expression significantly correlated with the infiltration level of MAIT cells.…”
Section: Discussionsupporting
confidence: 94%
“…We then examined the correlation between MR1 expression levels and GBM patients’ overall survival. We used data from TCGA and the Chinese Glioma Genome Atlas (CGGA) 17 and observed a significant negative correlation between MR1 expression levels and GBM survival (Figure_1b), with higher expressions of MR1 being associated with worse survival, in agreement with the previously reported prognostic value of MR1 expression in GBM 4 . We also investigated whether the observed association could be attributed to functional mutations in MR1 including the recently-reported loss of antigen presentation function of the substitution ( MR1 -R31H) in a human patient 18 , but found a very low frequency (0.06%) of genomic mutations in a range of glioma data sets including 3391 glioma samples, and none of which had the reported loss of function mutation MR1 -R31H (Figure_1c).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We have recently reported that the overexpression of MR1 correlates with a worse prognosis in patients with glioma [ 15 ]. Moreover, elevations in MR1 levels have been detected in CNS lesions of MS patients [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…MR1 is present on a variety of different cell types in numerous locations throughout the body [ 9 ] and we have recently shown that functional MR1 is expressed in the brain [ 14 ]. Moreover, its level directly correlates with a poor outcome in MS and glioma [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%